Numerical simulation of actuation processes and decoupling pyroshock of a pressure cartridge-type pin puller - Jingcheng Wang; Shihui Xiong; Yuquan Wen; Yadong Wang (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
In this study, a finite element model of a pressure cartridge-type pin puller is used to simulate the actuation process and predict the actuation shock using the deflagration equation of state and the fluid-structure coupling algorithm of the MSC/Dytran. The established model is validated by comparing the simulation results with the experimental results for pressure and actuation shocks. Based on the established finite element model, the contribution of the four shock sources to the actuation shock is quantitatively decoupled by changing the state of the pin puller. The results demonstrate that the maximum shock caused by the piston impact was 7454.33 G in the analysis frequency range of 500 Hz–10 kHz. The piston impact was the primary contributor to the actuation shock, accounting for approximately 80.80%. The contribution of the shock caused by payload release was approximately 18.56%. However, the total contributions of the shock generated by the pyrotechnic charge combustion and piston cutting off the shear pin were less than 1%. The conclusions of this study can provide a reference for the structural and shock-reduction design of pressure cartridge-type pyrotechnic separation devices.